2001
DOI: 10.1034/j.1600-0714.2001.300603.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in antifungal susceptibility of clones of Candida albicans isolated on single and sequential visits from a HIV‐infected southern Chinese cohort

Abstract: The increased frequency and severity of candidal infections in human immunodeficiency virus (HIV)-infected individuals has prompted the wide use of antifungals, such as amphotericin B, ketoconazole, and fluconazole, resulting in the emergence of drug-resistant strains of Candida albicans. To study this phenomenon in an ethnic Chinese cohort, we isolated multiple colonies of Candida from the oral cavities of 16 HIV-infected patients on single and subsequent sequential visits over a period of 12 months. Ten of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Altogether, there was no evidence in favor of the selection of resistant clones or the replacement of the original strain upon antifungal drug pressure in our study, suggesting that these events are rare in neutropenic leukemia patients receiving topical amphotericin B along with clear indications for systemic antifungals over a period of up to 6 months. This is in contrast with studies conducted in patients with human immunodeficiency virus infection, 20,40 which found that different subpopulations of colonizing or infecting strains could co-exist at a given time in the same patient and exhibit different patterns of susceptibility to antifungal drugs. We believe that such a discrepancy could reflect the different populations of patients studied (i.e.…”
Section: Discussioncontrasting
confidence: 52%
“…Altogether, there was no evidence in favor of the selection of resistant clones or the replacement of the original strain upon antifungal drug pressure in our study, suggesting that these events are rare in neutropenic leukemia patients receiving topical amphotericin B along with clear indications for systemic antifungals over a period of up to 6 months. This is in contrast with studies conducted in patients with human immunodeficiency virus infection, 20,40 which found that different subpopulations of colonizing or infecting strains could co-exist at a given time in the same patient and exhibit different patterns of susceptibility to antifungal drugs. We believe that such a discrepancy could reflect the different populations of patients studied (i.e.…”
Section: Discussioncontrasting
confidence: 52%
“…This, in turn, implies that subclones of C. albicans with variable genotypes may colonize the oral cavity simultaneously. In this event, it is difficult to determine with certainty the contribution, if any, of individual clones to infection (Soll et al ., 1988; Johnson et al ., 1995) and, further, the presence of more than one clonal type may have important therapeutic implications, as some may have different susceptibilities to antifungal agents (Korting et al ., 1988; Pfaller et al ., 1994; Samaranayake et al ., 2001). However, little is known of clonal variations in C. albicans during either recurrent episodes of oral candidiasis or asymptomatic carriage over prolonged periods in HIV disease.…”
mentioning
confidence: 99%
“…Microbiological samples were obtained using the concentrated oral rinse method previously described by Samaranayake et al Samples were inoculated on Sabouraud's chloramphenicol agar and incubated aerobically at 37°C for 48 hours. Presumptive identification of the Candida colonies isolated was carried out through Gram stain, germ tube test and culture on CHROMagar (Himedia).…”
Section: Methodsmentioning
confidence: 99%
“…Microbiological samples were obtained using the concentrated oral rinse method previously described by Samaranayake et al 7…”
Section: Microbiological Procedures and Identification Of Isolatesmentioning
confidence: 99%